ANALISIS PENGARUH LITERASI KEUANGAN DAN PERSONAL INTEREST TERHADAP KESADARAN INVESTASI PADA MAHASISWA MANAJEMEN UNIVERSITAS TIDAR ANGKATAN 2018 - Ridwan Adam; Alkadri Siharis (Lafadz Jaya Publisher, 2023)
This study aims to examine the effect of financial literacy and personal interest on investment awareness in Tidar University Management students. The data used in this study are primary data obtained from 30 respondents as a sample selected based on the simple random sampling method. The data obtained were then analyzed using correlation coefficient analysis and multiple linear regression using SPSS software version 25. The results of the analysis on the simultaneous test showed positive and significant results, which means that the independent variable has an influence on the dependent variable. While the partial test shows the results that the financial literacy variable has a significant positive effect on the investment awareness variable, but on the personal interest variable the results of the analysis show that the personal interest variable has an insignificant negative effect on the investment awareness variable. In the correlation coefficient test, the financial literacy variable on investment awareness has a perfect correlation, while the personal interest variable has a very weak relationship. The results of this study provide managerial implications for students who want to invest. students must instill a high interest in investing or it can be said that students must first have motivation in investing. By instilling student interest in investment, it is hoped that students will realize the importance of investment where we know that investment is a solution in today's era, the need is getting bigger and the cost of living is also getting higher.